Additive manufacturing of interpenetrating periodic open cellular structures (interPOCS) with in operando adjustable flow characteristics - Do, Giang; Geißelbrecht, Michael; Schwieger, Wilhelm; Freund, Hannsjörg (Chemical Engineering and Processing, 2020)
Structured catalyst supports and structured reactors offer interesting features to address heat and mass transport challenges in catalytic processes. The present work addresses the unique role of so-called interpenetrating periodic open cellular structures (interPOCS) as a geometrically flexible system enabling in operando adjustment of fluid flow characteristics. The interPOCS studied in this work consist of an interwoven structure of two POCS with a defined offset, each based on a diamond unit cell. The specific surface area and porosity, as the structures’ influential morphology parameters, were derived as a function of cell size and strut thickness, respectively. Both, POCS and interPOCS of different geometrical parameters were designed via computer-aided design, fabricated by fused deposition modeling and geometrically characterized. The influence of the structure offset and the geometrical dimension on the pressure drop was investigated in detail. From experimental data, the coefficients of an Ergun-type pressure drop correlation were fitted and a two cavity channel model was established to describe the dependency of the pressure drop on the offset position. The possibility of the structure shift in interPOCS represents a highly interesting and versatile option for in operando adjustment in catalytic processes.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Additive manufacturing; Flexible flow control; Flow field; Periodic open cellular structures (POCS); Pressure drop; Structured reactor